Pemanfaatan Peken Pinggul sebagai Media Edukasi Dalam Mendukung Pencapaian SDGs - Andi Muhammad Toha; Fadilah Nur Sugiyanto (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2026)
The implementation of the Community Service Program (KKN) in Melikan Village, Wedi District, Klaten Regency, carried the theme of stunting prevention by utilizing a local community event known as Peken Pinggul. This activity aimed to raise public awareness regarding stunting and provide free healthcare services accessible to all groups. The program was carried out in two sessions, namely the delivery of material on stunting (definition, symptoms, impacts, and prevention) and free medical check-ups, including blood pressure, blood sugar, height, and weight measurements. The results indicated a high level of community participation, enthusiasm for health services, and an increase in public knowledge about the importance of nutrition and healthy lifestyles in preventing stunting. This activity also directly supported the achievement of the Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty) through free health services, SDG 2 (Zero Hunger) through nutrition education, SDG 3 (Good Health and Well-being) through counselling and health examinations, SDG 6 (Clean Water and Sanitation) through education on sanitation importance, and SDG 17 (Partnerships for the Goals) through collaboration among students, village officials, community leaders, and the Peken Pinggul committee. Thus, Peken Pinggul has proven to be an effective medium for raising health awareness in a critically poor village while strengthening community-based sustainable development practices.